2019
DOI: 10.1016/j.compchemeng.2018.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A novel cost-effective silica membrane-based process for helium extraction from natural gas

Abstract: Natural gas reserves with 0.3-2 mol% helium are considered as the only viable source for this noble gas. Currently, cryogenic separation is used to extract helium, but it is energy-intensive. While membrane-based separation is a promising alternative, it is still not considered economical. Even for an inorganic/silica membrane with relatively high selectivity and permeance, a multi-stage membrane system with inter-stage compression is required, which necessitates high CAPEX and OPEX. This study proposes a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Process simulation of membrane technology for helium recovery from natural gas or other industrial gas sources has been widely studied and reported in the literature [28,37,[179][180][181][182][183]. Hägg et al compared three different types of membranes (i.e., porous silica, CMS, and Matrimid) for their applicability in helium recovery processes [179].…”
Section: Technology Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Process simulation of membrane technology for helium recovery from natural gas or other industrial gas sources has been widely studied and reported in the literature [28,37,[179][180][181][182][183]. Hägg et al compared three different types of membranes (i.e., porous silica, CMS, and Matrimid) for their applicability in helium recovery processes [179].…”
Section: Technology Advancesmentioning
confidence: 99%
“…Compared to Matrimid membrane, even though silica and CMS membranes are more expensive, the higher helium permeability coupled with higher He/CH4 and He/N2 selectivity still makes them more competitive. Moreover, Hamedi et al also reported a potential capital cost reduction of around 16-30 % using silica membrane system compared to polymeric membrane system, even though silica membrane's price is 60 times higher than polymeric membranes [181]. However, the challenges on the up-scaling of inorganic membranes needs to be addressed for the commercial application in helium recovery.…”
Section: Technology Advancesmentioning
confidence: 99%
“…Cryogenic liquefaction has been widely implemented for helium recovery from natural gas, while the high capital investment and energy consumption are the obstacles to the separation efficiency . Membrane-mediated helium recovery provides a potential alternative and has attracted increasing attention due to its high energy efficiency, absence of phase change, low environmental impact, small footprint, and ease of operation . Among many reported gas separation membrane materials such as metal–organic framework (MOF) membranes, silica membranes, and carbon molecular sieving membranes, polymer membranes have demonstrated great potential because of relatively low cost, robust mechanical properties, and excellent processability.…”
Section: Introductionmentioning
confidence: 99%
“…A two-stage membrane process as HeRU integrated with a single-column NRU was proposed by H. Hamedi et al [73,85], as shown in Figure 2.23. As presented in the schematic diagram, the NRU is supported by a heat-pump cycle to provide the process required refrigeration and 2-5% He produces from the NRU overhead column depending on the main feed gas.…”
Section: Hybrid Membrane-cryogenic Distillation Processmentioning
confidence: 99%
“…Instead of using a two-stage polymeric membrane, the overall cost can be reduced by a single-stage membrane utilizing a high selective (He/N2 selectivity 360) silica membrane proposed by the same author in another study shown in Figure 2.24 [85]. Their financial results showed that eliminating inter-stage compressor K-202 in process design shown in was observed many advantages compared to the two-stage process as compressor cost is the dominating cost factor.…”
Section: Hybrid Membrane-cryogenic Distillation Processmentioning
confidence: 99%